2021
DOI: 10.15403/jgld-2985
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sphere Size in the Context of Pancreatin Therapy for Exocrine Pancreatic Insufficiency: A Systematic Review

Abstract: While lipase content and appropriate acid protection of pancreatin preparations (PP) are well defined determinants of an effective therapy of exocrine pancreatic insufficiency, the optimal sphere size of PP has remained a matter of discussion. We performed a systematic review to assess the optimal sphere size of enteric coated pancreatin products that may best guarantee coordinated delivery of PP and food to the duodenum. PubMed was searched for studies on gastric emptying of indigestible spheres in the digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…1). hungsweise klinisch relevanten Vorteil sehen [8]. Dementsprechend sollte der klinische Erfolg einer Therapie im Vordergrund stehen.…”
Section: Exokrine Pankreasinsuffizienzunclassified
“…1). hungsweise klinisch relevanten Vorteil sehen [8]. Dementsprechend sollte der klinische Erfolg einer Therapie im Vordergrund stehen.…”
Section: Exokrine Pankreasinsuffizienzunclassified
“…Even if all Kreon particles showed a very narrow PSD and a rather round shape, it is questionable whether the particle size difference of 1 mm compared with Ermytal, Pangrol and Panzytrat in any way affects the efficiency of the PERT. It is true that the European guideline [ 4 ] recommends particles smaller than 2 mm, but it has only recently been demonstrated that there is no scientifically sound evidence for this cut-off value, which needs serious re-evaluation [ 5 ].…”
mentioning
confidence: 99%
“…Prof. Dr. Karl-Uwe Petersen mentions that the conclusion of the abovementioned HaPanEU guideline [ 3 ] has been challenged, particularly in his systematic review from March 2021 [ 4 ], which succeeds our publication; however, the authors would like to point out that the systematic review is based on publications currently in the public domain and is not reflective of the full dataset for our particular study and the pancreatin preparations available in Russia/Commonwealth of Independent States (CIS). Additionally, contrary to what is being postulated and as mentioned in the publication by Prof. Dr. Karl-Uwe Petersen; the pancreatin preparations assessed, including Kreon, do not have a round shape but rather a more cylindrical shape, where the Feret min diameter represents the diameter of the cylinder and the Feret max represents the maximum size of the particle in any dimension, thereby being indicative of the probability of the particle passing the pylorus together with the chyme.…”
mentioning
confidence: 99%
“…We also note that Prof. Dr. Karl-Uwe Petersen only addresses the PSD and the max Feret X value in his Letter to the Editor [ 4 ], and does not comment on the other differences between the specific pancreatin preparations identified in our in vitro investigation, particularly the differences observed regarding lipase activity (with Micrazim 40000 being a significant outlier at 79% of the declared lipase content) and (associated) dissolution [ 2 ] - variables likely having an even greater impact on digestive potency and clinical efficacy.…”
mentioning
confidence: 99%